Scorpia rising - Horowitz, Anthony, 1955- (London : Walker Books, 2011)
Alex Rider must once again do battle against the terrorist organization responsible for the death of his parents--Scorpia--when their plot in the Middle East poses a threat to humanity, but this time around the risks are bigger and Alex will not walk away so easily.
"Alex Rider mission 9.
5.0
5-8.
5-8
Keywords: Orphans -- Juvenile fiction; Terrorism -- Juvenile fiction; Orphans -- Fiction; Spies -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; Spy stories; Terrorism -- Fiction; England -- Juvenile fiction; London (England) -- Juvenile fiction; Middle East -- Juvenile fiction; England -- Fiction; London (England) -- Fiction; Middle East -- Fiction; England -- Fiction; London (England) -- Fiction; Middle East -- Fiction; Spy stories